Religious Objection to Cantharidin Use in Jain Patients. Issue 3 (1st March 2012) - Patel, Devika; Shwayder, Tor
Abstract : Abstract: We report a case of a Jain family that was upset with the use of cantharidin for treatment of molluscum contagiosum for religious reasons.